APPLICATION OF INTEGRATED MULTI TROPHIC AQUACULTURE SYSTEM MODEL TO REDUCE WASTE ORGANIC MATERIALS - Palinussa, Eilzabeth; Pattinasarany, Maureen M; Ririhena, John Etry (Universitas Mataram, 2025)
ABSTRACT The use of intensive aquaculture systems is one of the activities that provide an overview of aquaculture to increase production due to the high stocking density of fish but has an impact on the contribution of waste from fish farming. Overcoming existing problems with the application of the Integrated Multi Trophic Aquaculture system cultivation model, this system is expected to help reduce cultivation waste. The purpose of this study is to determine how the IMTA system can help reduce organic waste in the aquatic environment so that water quality can be maintained and suitable for the life of organisms. This research was conducted from June to July 2023, at the Center for the Study and Development of Regional Excellence and Empowerment of Coastal Communities. The method used was descriptive quantitative. The results of the TOM analysis value in all treatments decreased. in treatment A 21.1 mg/l, B 41.0 mg/l and C 34.7 mg/l. TSS decreased differently every time, especially on day 42 for treatment A 0.031 mg/l, B 0.023 mg/l and C 0.178 mg/l. Ammonia for day 42 also decreased, namely in treatment A 0.03 mg/l, B 0.20 mg/l, C 0.13 mg/l. On day 42 nitrate for treatment A 0.03 mg/l, B 0.06 mg/l, C 0.08 mg/l. Water quality parameters for temperature, salinity, dissolved oxygen and acidity had reasonable values for all biota reared. Conclusion The IMTA system can help reduce organic waste of TOM, TSS, ammonia and nitrate, in addition, it can also reduce the amount of organic waste